2019
DOI: 10.3748/wjg.v25.i20.2416
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing radiotherapy with immune checkpoint blockade in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer, and its incidence is rapidly increasing in North America and Western Europe as well as South-East Asia. Patients with advanced stage HCC have very poor outcomes; therefore, the discovery of new innovative approaches is urgently needed. Cancer immunotherapy has become a game-changer and revolutionized cancer treatment. A comprehensive understanding of tumor-immune interactions led to the development of immune checkpoint inhibitors (ICIs) as new the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 122 publications
0
67
0
Order By: Relevance
“…could reinvigorate anti-tumor immunity [50]. Recently, nivolumab and pembrolizumab, two therapeutics against PD-L1/PD1, have been recently approved for subsequent-line therapy [51].…”
Section: Discussionmentioning
confidence: 99%
“…could reinvigorate anti-tumor immunity [50]. Recently, nivolumab and pembrolizumab, two therapeutics against PD-L1/PD1, have been recently approved for subsequent-line therapy [51].…”
Section: Discussionmentioning
confidence: 99%
“…143,146 Most of the previous randomised clinical trials that tested the combination of systemic therapy and locoregional therapy for HCC, either concurrent or sequential, failed to demonstrate a survival benefit of combination therapy. [147][148][149][150][151][152][153][154][155] The post-randomisation confounding factors previously mentioned contributed greatly to the failure of these trials. About 10 to 20% of patients randomised to the locoregional therapy arm of the clinical trials could not receive the assigned treatment because of technical difficulties.…”
Section: Optimal Management Of Immune-related Adverse Eventsmentioning
confidence: 99%
“…In human cancers, the presence of T SCM or T RM cells is associated with better survival, and two studies reported that these populations seem to be particularly mobilized during anti-PD-1 therapy [ 102 , 117 ]. The rationale of combining immunogenic therapies to ICPi led to several clinical trials testing different associations in multiple cancers [ 170 , 171 , 172 , 173 , 174 ]. While clinical studies tend to confirm, at least in some cancer types, the benefit that such combinations bring to patients, the results clearly indicate that improvements are still required to fully exploit the potential of combined therapies while limiting their immune-related toxicity.…”
Section: Discussionmentioning
confidence: 99%